Review of forensically important entomological specimens collected from human cadavers in Malaysia (2005-2010) - Kavitha, R.; Nazni, W.A.; Tan, T.C.; Lee, H.L.; Sofian-Azirun, Mohd (2013)
Forensic entomological specimens collected from human decedents during crime scene investigations in Malaysia in the past 6 years (2005-2010) are reviewed. A total of 80 cases were recorded and 93 specimens were collected. From these specimens, 10 species of cyclorrphagic flies were identified, consisting of Chrysomya rufifacies (Macquart) -38 specimens (40.86), Chrysomya megacephala (Fabricius) -36 specimens (38.70), Chrysomya villeneuvi (Patton) -2 specimens (2.15), Chrysomya nigripes (Aubertin) -2 specimens (2.15), Chrysomya pinguis (Walker) -1 specimen (1.08), Hermetia illucens (Linnaeus) -1 specimen (1.08), Hemipyrellia liguriens (Wiedemann) -5 specimens (537), Synthesiomyia nudiseta (Wulp) -1 specimen (1.08), Megaselia scalaris (Loew)-1 specimen (1.08) and Sarcophaga ruficornis (Fabricius) -4 specimens (4.30). In two specimens (2.15), the maggots were not identifiable. Ch. megacephala and Ch. rufifacies were the commonest species found in human decedents from three different ecological habitats. S. nudiseta is an uncommon species found only on human cadavers from indoors. A total of 75 cases (93.75) had a single fly infestation and 5 cases (6.25) had double fly infestation. In conclusion, although large numbers of fly species were found on human decedents, the predominant species are still those of Chrysomya. (C) 2013 Elsevier Ltd and Faculty of Forensic and Legal Medicine. All rights reserved.